2017
DOI: 10.14419/ijet.v7i1.1.10821
|View full text |Cite
|
Sign up to set email alerts
|

Speech controlled home mechanization framework using android gadgets

Abstract: This task displays the development Speech Controlled Home Mechanization Framework Using Android Gadgets of home apparatuses in light-weight of voice order utilizing humanoid. This technique has been meant to help and provides the help to senior and unfit individual’s reception. Recent voice based applications provide acknowledges the voice contribution from the advanced transportable. During this venture, the voice input has been caught by the ports and might be sent to the Arduino Uno. HC 05 module in Arduino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Speech recognition is useful in many domains, like security and the speech-controlled home mechanization framework [21]. The voice of a person is a valuable biometric feature and can be used for identity verification [22].…”
Section: Related Workmentioning
confidence: 99%
“…Speech recognition is useful in many domains, like security and the speech-controlled home mechanization framework [21]. The voice of a person is a valuable biometric feature and can be used for identity verification [22].…”
Section: Related Workmentioning
confidence: 99%
“…They have taken DATAMALL datasets for the experiment and have demonstrated that this approach gives higher accuracy and classifies at greater speed. Nurul et al, [12] has done an analysis on Naive Bayes Classifier across different Datasets. The authors have incorporated SPAMBASE and Spam Data for their experiment using WEKA tool.…”
Section: Literature Surveymentioning
confidence: 99%
“…Forensics now-a-days are enforcing its impact and need in many diverse areas like software affected during natural disasters [14], cloud applications where the third party storage kind of works related [16], medicine [17] [19] and other diverse application areas [15] [18][19] [20].…”
Section: Introductionmentioning
confidence: 99%